1996
DOI: 10.1021/ma9511964
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Chain Organization in Ultrathin Poly(di-n-hexylsilane) Films

Abstract: The effect of film thickness on the organization kinetics of ultrathin (50-1000 Å thick) spin-cast polymer films was studied using poly(di-n-hexylsilane) and UV absorption spectroscopy. We found an extensive reduction in the crystallinity as well as a reduction in the rate of crystallization for film thicknesses below 500 Å resulting from the constrained geometry. Modeling using polymer crystallization theories elucidated the surface-induced phenomena. We found that the dimensionality of the growth depended bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
175
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(194 citation statements)
references
References 26 publications
14
175
0
Order By: Relevance
“…Disorder in the presence of the SiO 2 interface has been observed previously in P3HT films 17 and in other non-conjugated polymers. 38 The benefits of the silane treatment on P3HT microstructure likely arise due to the interactions of the alkyl chains in the polymer with those of OTS. 37 As a result, the density of interface nucleated crystallites on an OTS-treated surface is approximately twenty times higher than on bare SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Disorder in the presence of the SiO 2 interface has been observed previously in P3HT films 17 and in other non-conjugated polymers. 38 The benefits of the silane treatment on P3HT microstructure likely arise due to the interactions of the alkyl chains in the polymer with those of OTS. 37 As a result, the density of interface nucleated crystallites on an OTS-treated surface is approximately twenty times higher than on bare SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a decreasing film thickness could reduce the mobility of the polymer chains hindering the incorporation of new stems to the crystal growth front and contributing to the delayed crystallization kinetics observed. Other studies in confined polymers also attribute the delayed crystallization kinetics to changes in the nucleation step [18,19]. For instance, a decrease in the number of nuclei has been proposed to occur for films with thicknesses in the range of the critical nuclei size [19].…”
Section: Influence Of Crystallization Temperature On the Development mentioning
confidence: 99%
“…In particular, for polymer systems it has been found that confinement can change the glass transition temperature [1][2][3][4], molecular mobility [5,6], behaviour of the phases and morphology [7,8], molecular orientation [9] and crystallization behaviour [10][11][12][13]. Polymeric materials can be subjected either to chemical or to physical confinement.…”
Section: Introductionmentioning
confidence: 99%